In vitro antimicrobial,cytotoxic and anti-cancer activity from cocos nucifera oil - Rosshazeela, Binti Roslan. (Universiti Malaysia Sarawak (UNIMAS), 2007)
In vilro evaluation of antimicrobial, cytotoxic and anti-cancer activity of Cocos nucifera oil has been carried out. Copra oil (CO) and virgin coconut oil (VCO) was extracted with methanol with the ratio 3: I and I: I respectively. Bioassay testing on Artemia salina was earried out for both CO and VCO methanol extraet to evaluate their eytotoxicity at the concentration; I, 10 and 100 ppm. The data revealed that LCso value for copra oil methanol extract was less than 1 ppm while LCso value for virgin coconut oil methanol extract was less than 10 ppm. Moreover, both methanol extract at three different concentrations 10, 50 and 100 ppm were further tested against three types of fungal; Aspergillus /umigalus, Aspergillus flavus and Aspergillus sydowii. The result showed that CO and VCO methanol extract exhibited inhibition to these three types of fungus with different inhibition concentrations. Antibacterial bioassay was also conducted for both methanol extract. Escheria coli and Pseudomonas fulgida were both gram negative bacteria and devoid from activity for both extract. Methanol extract of VCO at 0.1 and I ppm were also further tested on nasopharyngeal cancer (NPC) ccll lines. These are significant inhibition of VCO MeOH extract against NPC at concentration of 0.1 and 1 ppm.